Harvesting Charges for Florida Citrus: Picking, Roadsiding, and Hauling, 2015/16 - Ariel Singerman; Marina Burani-Arouca; Stephen H. Futch (EDIS)
This article summarizes the harvesting charges for citrus during the 2015/16 season and it also documents the changes in harvesting costs as the impact of HLB increases across the state. On-tree prices are the basis for establishing the economic return to citrus growers. Therefore, the usefulness of the estimates we presented resides in that they provide the basis for computing on-tree prices from delivered-in prices; allowing to compute the change in citrus growers’ economic returns as the industry adapts to remain profitable.